MiR-140-5p mediates bevacizumab-induced cytotoxicity to cardiomyocytes by targeting the VEGFA/14-3-3γ signal pathway. Issue 6 (19th September 2019) - Chen, Xuan-Ying; Huang, Wei-Lin; Peng, Xiao-Ping; Lv, Yan-Ni; Li, Jun-He; Xiong, Jian-Ping
Graphical Abstract: Abstract: Bevacizumab (BVZ) is the first recombinant humanized monoclonal antibody against vascular endothelial growth factor (VEGFA) approved by the FDA for the treatment of different kinds of cancers, especially colorectal cancer. Although the anti-tumor effects have been verified, the side effects of BVZ are also noteworthy, among which, cardiotoxicity may be the most serious side effect of BVZ. However, the exact mechanisms of cardiotoxicity induced by BVZ have been little explored. This study was conducted in vitro in a human cardiac myocyte (HCM) model. MTT assay was conducted to determine BVZ-stimulated cell viability. For testing the function and mechanism, the cells were transfected with miR-140-5p mimics, miR-140-5p inhibitor and/or VEGFA small interfering RNA (si- VEGFA ). Then, apoptosis of the cells was detected via annexin V/propidium iodide (AV-PI) staining followed by flow cytometry. qRT-PCR and western blot assays were applied to measure gene expression ( i.e. mRNA) and protein levels, respectively. The CK, LDH, SOD, CAT and GSH-Px activities and MDA level were determined using commercial kits. ROS levels were determined by DCFH-DA assay. Mitochondrial membrane potential was measured by JC-1 assay. Dual-luciferase reporter assay was used to detect the interaction between miR-140-5p and VEGFA . BVZ could inhibit HCM proliferation and induce apoptosis. miR-140-5p was upregulated in response to BVZ treatment and miR-140-5p restraint could alleviate HCM damage caused by BVZ treatment. In contrast, VEGFA and 14-3-3γ expressions were down-regulated by BVZ, and miR-140-5p could inhibit the expression of 14-3-3γ by directly targeting VEGFA . Moreover, VEGFA suppression enhanced HCM injury stimulated by BVZ and partially reversed the functional role of the miR-140-5p inhibitor in BVZ-treated cells. Taken together, miR-140-5p promoted BVZ-treated cardiomyocyte toxicity by targeting the VEGFA /14-3-3γ signal pathway. Collectively, miR-140-5p mediated the BVZ-induced cytotoxicity to cardiomyocytes by targeting the VEGFA /14-3-3γ signal pathway, indicating that miR-140-5p may be a novel target for treating BVZ-induced cardiotoxicity.